A simple gadget to guide a person to adopt good standing and sitting posture - Lim, Shawn Jun Wei (Nanyang Technological University, 2020)
Good Posture is defined as the position where an individual has a balanced and upright posture. For a good posture to be determined, a straight line should be able to be drawn downwards from the earlobes to the ankle from the side profile. The lack of a good posture will result in not only back pain but also neck strains. Therefore, it is important and necessary to maintain a good posture at all times. The entirety of the report will cover the design and development of a simple gadget that will allow the user to detect when the good posture has been compromised by the user. The author will begin by creating a functional analysis diagram and thereafter a morphological chart based on the flow functions as planned in the functional analysis diagram. After the morphological chart, three design ideas will be generated from the chart and evaluated through the weighted matrix formula to determine which design has the highest score to be the perfect choice for further development. The final product will focus on alerting users in a non intrusive manner that allows for the user to know if his or her posture has veered off the correct posture. The final product will also be tested ad built in real-life to test in various scenario to ensure that the basic requirements are met and evaluate the limitations and discussions for future development of the final product.